Safety culture among operating room healthcare workers: still a long way to go. An analytical cross-sectional study from Turkey - Filiz, Emel (Revista Cuidarte, 2023)
Highlights: Studies show that the level of safety culture of health workers is not at the desired level and progress is very slow. Similar to the first evaluation 10 years ago in Turkey, the patient safety culture level of operating room health professionals was found to be low (41%). Compared to the previous study, there was a positive change in 8 dimensions and a negative change in 3 dimensions. There was no change in a dimension. Lowest average percentage of positive responses were “frequency of events reported (18%)” and “non-punitive response to error (19%). The scores of all 12 dimensions were lower than the AHRQ score. Introduction: safety culture attitudes of health workers are still not at the desired level. Although the creation of patient safety culture is important for all health care environments, it is more vital for critical units. Objective: to determine the patient safety culture levels of those working in the operating room environment and compare them with the 2008 results of the same hospitals. Materials and Methods: an analytical cross-sectional study was conducted in 2017-2018. The Turkish version of the Hospital Survey on Patient Safety Culture was administered to nurses, anesthesia technicians, assistant physicians, and specialist physicians working in the Operating Rooms (n=258) of two university hospitals in Konya, a large city in Anatolian region of Turkey. Results: average percent positive response to the 42 items was low (41%, n=258). While there was no change in one dimension of the questionnaire compared to 2008; there was a positive change in 8 dimensions and a negative change in 3 dimensions. All 12 dimensions were lower than the Agency for Healthcare Research and Quality score. Discussion: Despite many studies, policy developments and interventions on patient safety, the improvement of a patient safety culture is very slowly in Turkey as in other countries. Conclusion: non-reporting of errors and a punitive approach in case of errors are still considered the most important problems. How to cite this article: Fíliz Emel. Safety culture among operating room healthcare workers: still a long way to go. an analytical cross-sectional study from Turkey. Revista Cuidarte 2023;14(2):e2872. http://dx.doi.org/10.15649/cuidarte.2872